2022
DOI: 10.5603/fhc.a2022.0002
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of IL-8 and Wnt2 is associated with prognosis of gastric cancer

Abstract: This article has been peer reviewed and published immediately upon acceptance.It is an open access article, which means that it can be downloaded, printed, and distributed freely, provided the work is properly cited. Articles in "Folia Histochemica et Cytobiologica" are listed in PubMed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…IL-8 is a versatile cytokine that has been shown to promote angiogenesis, attract immune cells, and stimulate tumor growth, invasion, and migration through both autocrine and paracrine effects [60][61][62]. Previous research has also shown that IL-8 can serve as a biomarker associated with a poor prognosis and chemoresistance for various types of cancer [63,64]. Additionally, IL-8 has been linked to adverse outcomes in brain tumors [65] and breast cancer [66].…”
Section: Discussionmentioning
confidence: 99%
“…IL-8 is a versatile cytokine that has been shown to promote angiogenesis, attract immune cells, and stimulate tumor growth, invasion, and migration through both autocrine and paracrine effects [60][61][62]. Previous research has also shown that IL-8 can serve as a biomarker associated with a poor prognosis and chemoresistance for various types of cancer [63,64]. Additionally, IL-8 has been linked to adverse outcomes in brain tumors [65] and breast cancer [66].…”
Section: Discussionmentioning
confidence: 99%
“…High level of IL8 expression was observed in many human cancers, including breast, lung, prostate, pancreatic, colorectal, esophageal cancers as well as melanoma and numerous studies have shown that serum level of IL-8 in cancer patients can act like a prognostic marker [21-25]. Increased IL8 expression was observed in gastric cancer tissue and overexpression of IL-8 was reported to have association with prognosis of this cancer [26]. Higher level of IL8 was also reported in the sera of liver, gastric and non-small-cell lung cancer patients as compared to healthy controls [27].…”
Section: Discussionmentioning
confidence: 99%
“…Interleukin-8 (IL-8) is a pro-inflammatory, angiogenic chemokine that plays a fundamental role in immune modulation within breast cancer TME [ 9 ]. Overexpression of IL-8 is associated with the oncogenic signaling pathways, increased tumor growth, metastasis, and poor prognosis [ 10 ]. Moreover, the cytokine profile of tumor-associated macrophages showed that IL-8 is the most abundant cytokine released in advanced breast cancer patients [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Overexpression of IL-8 is associated with the oncogenic signaling pathways, increased tumor growth, metastasis, and poor prognosis [ 10 ]. Moreover, the cytokine profile of tumor-associated macrophages showed that IL-8 is the most abundant cytokine released in advanced breast cancer patients [ 10 ]. In this regard, utilizing neutralizing antibody against IL-8 was revealed to decrease tumor growth, angiogenesis, and metastasis [ 11 ].…”
Section: Introductionmentioning
confidence: 99%